The Influence of Seni Kriya Rotan Media with Project Based Learning Model on Improving Procedural Text Writing Skills - Selfiana Kurniasari; Lintang Kironoratri; Nur Fajire (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Improving procedural text writing skills in elementary school students is an important aspect in Indonesian language learning because it is related to the ability to organize steps in a coherent, logical, and systematic manner. The activity was carried out in one of the elementary schools in the local district in the odd semester of the 2025/2026 academic year. The population in this activity was all fourth-grade students, with a sample of 30 students selected using a purposive sampling technique. The instruments used included a procedural text writing skills test, an observation sheet to determine student activities during learning, and documentation as supporting data. Data analysis was carried out using quantitative descriptive techniques by comparing the results before and after the application of the treatment to determine whether there was an increase in student abilities. The results obtained showed that there was an increase in procedural text writing skills after the implementation of appropriate learning media. This was seen from the increase in the average student grades from the initially sufficient category to the good category. In addition, student learning activities also experienced an increase as indicated by active participation in learning, the ability to organize steps systematically, and the accuracy of language use. These findings indicate that the use of appropriate learning media can have a positive impact on students’ writing skills and create a more active, effective, and meaningful learning atmosphere. Therefore, the use of learning media can be used as an alternative strategy to improve the quality of learning in elementary schools.